Superior transverse piezoelectricity in organic-inorganic hybrid perovskite nanorods for mechanical energy harvesting. (August 2021) - Khan, Asif Abdullah; Huang, Guangguang; Rana, Md Masud; Mei, Nanqin; Biondi, Margherita; Rassel, Shazzad; Tanguy, Nicolas; Sun, Bin; Leonenko, Zoya; Yan, Ning; Wang, Chunlei; Xu, Shuhong; et al.
Abstract: Developing highly piezoelectric nanoparticles (NPs) with inherent mechanical-electrical coupling effect is critically important for energy harvesters, self-powered sensors and actuators. Over the past decades, the NPs with a high longitudinal piezoelectric coefficient (d33 ) were developed for piezoelectric nanogenerators (PENGs) that operate under periodic vertical compression mode. As an alternative, high-performance PENGs can be developed by taking advantage of materials with a superior transverse piezoelectric coefficient (d31 ). In this work, we successfully synthesized an organic-inorganic hybrid perovskite (OIHP) nanorods (NRs) of (4-aminotetrahydropyran)2 PbBr2 Cl2 [(ATHP)2 PbBr2 Cl2 ] that exhibits a large d31 of 64.2 pC/N, which is 3 times higher than the well-known poly (vinylidene fluoride) (PVDF) polymer (21 pC/N). A saturated polarization of 5.4 μC/cm 2 and a piezoelectric voltage coefficient (g33 ) of 900 mVm/N are also reported. The (ATHP)2 PbBr2 Cl2 NRs can be dispersed homogeneously in a polymer matrix to make piezoelectric composite films. Due to their excellent flexibility, uniform dispersion and large surface area the concurrent vertical strain and lateral bending yield a high piezoelectric performance. We fabricate a unique piezoelectric composite film for PENGs, which can produce an output voltage (Voc ) of 90 V and a short-circuit current (Isc ) of 6.5 μA under an applied force of only 4.2 N, outperforming a number of the state-of-the-art PENGs (Table S2 ). The harvested electrical energy is stored in a capacitor by a two-stage energy transfer mechanism for self-powered electronics. This is the first work, that not only reveals the large transverse piezoelectricity in the (ATHP)2 PbBr2 Cl2 NRs, but also coins a route to employ it in practical energy harvesting devices. Graphical Abstract: ga1 Highlights: Synthesis of (ATHP)2 PbBr2 Cl2 hybrid perovskite nanorods (NRs) for mechanical energy harvesting applications. The nanorods exhibit a transverse piezoelectric coefficient (d31 ) of 64.2 pC/N, 3-times higher than the PVDF film. The (ATHP)2 PbBr2 Cl2 @PDMS film generates an output voltage of 90 V and a current of ~ 6.5 μA with an applied force of 4.2 N. The PENGs can charge a 1 μF capacitor to 5.5 V in 20 s and promising to be integrated with the electronic circuits.